Radicalism and Multicultural Awareness Among College Students: A Comparative Study of Cross-Cultural Student Perceptions - Sormin, Salman Alparis; Harahap, Dharma Gyta Sari; ., Jamaris; Rochmat, Saefur; Irawan, Ferry; Rafi’y, Muh.; Tembang, Yonarlianto; Riwu, Lay (International Journal of Membrane Science and Technology, 2023)
The issue of radicalism is an inseparable part of the campus world with an academic environment consisting of various students with diverse cultures. Various kinds of cultural diversity in the social environment have different perspectives in applying social values. The research conducted aims to determine students' initial perceptions of radicalism and multicultural awareness among cross-cultural students at Musamus University, Merauke. The instrument was developed based on the integration of multicultural awareness values with student radicalism profiles which consist of five main indicators which are derived into several sub-indicators. The instruments developed have been validated by expert validators in determining the validity of the content, constructs according to the indicators that will be measured in the research process. Students fill out a questionnaire within the scope of their perspective regarding the profile of radicalism. Furthermore, the data collected was tested for validity and practicality based on the validity coefficient and the Cronbach Alpha value. The results of the analysis show that the instruments used in the research process have met the criteria of validity and practicality. Further analysis was carried out using the Chi-Square test to determine the distribution of respondent profiles in measuring perceptions of radicalism based on multicultural values. The results of the study show that the cultural diversity possessed by each student is a very influential factor in understanding the basic perspectives on radicalism and multicultural awareness in the social environment.